Morpho-Physiological Responses of Selected Vegetables in Hydroponic and Soil-Based Systems Under Climatic Stress - Syeda Zoia Ali Zaidi; Shaheen Begum; Mehwish Jamil Noor; Gul-e-Saba Chaudhry; Shahbaz Khan; Muhammad Adnan (Tropical Life Sciences Research, 2025)
An extreme climatic change due to anthropogenic activities causes disruptions in ecosystems and threatens the planet’s overall balance. Hydroponic is smart and sustainable agriculture practice that aims to produce two times more yield than traditional practices. To investigate the efficiency of hydroponics technique, the morpho-physiological responses of selected vegetable species were analysed. Tomato (Solanum lycopersicum L.), Eggplant (Solanum melongena), Lettuce (Lactuca sativa), Green Chili (Capsicum annuum) and Okra (Abelmoschus esculentus) were selected for the experiment. Soil nutrients analysis and hydroponics nutrients uptake analysis were also carried out side by side using UV-Visible Spectroscopy, Atomic Absorption Spectroscopy and Titration method. In hydroponic water analysis, it was found that 42% of supplied Cl- had been taken up by the plants whereas 79% of all supplied Zinc and Iron had been taken up by the plants. The uptake percentages of other anions and cations ranged between 45% to 62%. Morpho-physiological responses of Lettuce and Tomato in soil-based and hydroponic experiments were almost similar. Whereas, hydroponically grown Okra, Green Chili and Eggplant showed maximum height, roots length, number of leaves and weight. Overall findings showed that hydroponic system was more efficient in terms of crops yield, water usage and environmental contamination. Thus, it is recommended to increase the duration of experiment in future to further verify the climatic change effects.